2021
DOI: 10.1007/s11695-021-05555-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the One Anastomosis Gastric Bypass with Various Biliopancreatic Limb Lengths: a Retrospective Single-Center Cohort Study

Abstract: Introduction One anastomosis gastric bypass (OAGB) is an effective and safe treatment for morbidly obese patients. Longer biliopancreatic (BP) limb length is suggested to result in better weight loss outcomes, but to date, no data are available for the OAGB to substantiate this. We hypothesized that applying a longer BP-limb length in the higher BMI classes would result in more weight reduction so that the attained BMI would be comparable to patients with a lower BMI, thereby compensating for dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…For instance, in the current study, seven original research papers have been referred to about the relationship between limb length and the result of surgery. The method of measurement was not disclosed in five studies (3,(12)(13)(14)17). In one study, a rubber band was used for measurement (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the current study, seven original research papers have been referred to about the relationship between limb length and the result of surgery. The method of measurement was not disclosed in five studies (3,(12)(13)(14)17). In one study, a rubber band was used for measurement (15).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that OAGB with a 200 cm biliopancreatic limb was associated with a higher rate of protein-calorie malnutrition compared to a 160 cm biliopancreatic limb. Slagter et al ( 13 ) found that attained BMI was higher in OAGB patients with a 200 cm biliopancreatic limb compared to those with a 150 cm or 180 cm biliopancreatic limb. Shah et al ( 14 ) investigated the outcome of LRYGB based on the total length of the alimentary and biliopancreatic limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies agreed that biliopancreatic limb <200 cm is associated with lower nutritional deficiencies, and different lengths of biliopancreatic limb had comparable BMI loss and comorbidities resolution (6)(7)(8)(9)(10) .…”
Section: Introductionmentioning
confidence: 98%
“…Mean %TWL is 32% at 1–2 years, then decreases slightly to 25% at 10 years and maintains this up to 20 years post-op [ 4 ]. Many clinical trials that compared different limb lengths of gastric bypass have not shown significant differences in weight loss [ 5 ]. Despite excellent weight loss, a percentage of patients still fail to lose 50% excess weight loss or reach a BMI of less than 35 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%